Late Quaternary Kinematics and Deformation Rate of the Huoyanshan Structure Derived From Deformed River Terraces in the South Piedmont of the Eastern Chinese Tian Shan - Yang, Xue; Wu, Chuanyong; Li, Zhigang; Wang, Weitao; Chen, Gan; Duan, Lei (Frontiers in Earth Science, 2021)
The deformation pattern and strain partitioning in the Eastern Chinese Tian Shan are poorly known because of the lack of quantitative study of the kinematics and deformation rate of the major structure. Here we report a late Quaternary shortening rate for the most active reverse fault-and-fold in the Eastern Chinese Tian Shan. We quantified the kinematics and late Quaternary shortening rate of the Huoyanshan structure based on detailed high-resolution remote sensing image interpretations, field investigations and geological mapping. Six generations of folded terraces along the Tuyugou valley that showed the progressive folding process by the Huoyanshan structure were identified. A kinematic model of curved thrust fault propagation and folding allowed us to describe the terrace deformation pattern and subsurface fault geometry and calculate shortening across this structure. Combined with a regional age control of terrace T4 in the Tuyugou valley, a late Quaternary shortening rate of 2.0–3.2 mm/yr of the Huoyanshan structure was obtained. This is a relatively high shortening rate in the whole Eastern Chinese Tian Shan (roughly east of 88 E). This shortening rate of the Huoyanshan structure highlights that the ongoing India and Eurasia collision has affected the entire Tian Shan but shows two strain partitions: the main strain-absorption belt is located within the Eastern Chinese Tian Shan interior, but strain also occurs at the range-front foreland in the Western Tian Shan.